CONSUMER DECISION-MAKING IN DIGITAL THRIFTING: ANALYZING THE ROLE OF PRICE, VALUE PERCEPTION, AND LIFESTYLE FACTORS ON TIKTOK SHOP - Agustin, Amalia Hikmah; Fatimah, Feti; Hafidzi, Ahmad Hasan (Univesitas Muhammadiyah Tangerang, 2025)
This study investigates the growing phenomenon of thrifting (second-hand shopping) on TikTok Shop, examining how price, perceived value, and lifestyle influence purchasing decisions in this emerging social commerce platform. The research addresses a critical gap in understanding digital-native consumption patterns, particularly in developing markets where thrifting represents both an economic choice and lifestyle statement. Using an explanatory research design, data was collected from 100 active TikTok Shop users through purposive sampling, with validated questionnaires measuring key variables. Analysis involved rigorous statistical testing including multiple linear regression and coefficient of determination. The findings reveal that all three factors significantly impact thrifting purchases: price sensitivity demonstrates strong influence, followed by perceived value and lifestyle congruence. Notably, these variables collectively explain a substantial portion of purchase decision variance, highlighting their interconnected effects in social commerce environments. This study contributes novel insights by being among the first to explore thrifting behavior specifically within TikTok Shop's unique ecosystem, revealing how traditional economic factors interact with contemporary lifestyle values in digital marketplaces. The results advance theoretical understanding of sustainable consumption in social commerce contexts while offering practical guidance for marketers seeking to engage the thrifting demographic through platform-specific strategies that balance affordability, value perception, and lifestyle alignment.